Pengaturan Pembayaran BPHTB pada Akta Perjanjian Pengikatan Jual Beli Notaril - Wahyuni, Fitri (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The transfer of rights (sale and purchase) of land in Indonesia is regulated in severalpositive laws that are currently in force. The latest legislation is Government Regulation No. 35 of 2023 (PP 35/2023) concerningGeneral Provisions on Regional Taxes and Levies, which regulates the payment ofLand and Building Acquisition Rights (BPHTB)Acquisition of Land and Building Rights Tax (BPHTB) is also imposed onSale and Purchase Agreements (PPJB) made by and before a notary.The PPJB referred to is a paid-up PPJB, but this is still not in line withthe laws and regulations that require the payment of BPHTB on the Deed of Saleand Purchase (AJB) made by and in the presence of a Land Deed Official (PPAT)as a basic requirement for the name on the certificate of land and building rightsrequired by the National Land Agency. This research adopts normative legal research by examining literature and the legal norms contained in laws and regulations. The results show that regarding PP 35/2023 concerning General Provisions on Regional Taxes and Regional Levies mentioned above, there is still a need for legal clarity thatallows the notarial PPJB to be used as a requirement for the transfer ofownership of land certificates by buyers.